2017
DOI: 10.4103/0970-2113.201299
|View full text |Cite
|
Sign up to set email alerts
|

Study the association of chronic obstructive pulmonary disease with early endothelial dysfunction and its impact on cardiovascular system by estimating urinary albumin creatinine ratio

Abstract: Background:Chronic obstructive pulmonary disease (COPD) attribute to systemic inflammation which is responsible for microalbuminuria reflecting endothelial dysfunction, could be a significant surrogate marker of potential cardiovascular morbidity.Objective:The aim of our study was to find out the possible association of COPD with early cardiovascular changes in the form of renal endothelial dysfunction.Settings and Design:Case–control, multi-group, cross-sectional hospital-based study was designed and conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…13 In the study of Mehmood and Sofi et al, and Agrawal et al, COPD patients having microalbuminuria were more hypoxic than those of COPD patients without microalbuminuria and it was inversely related to PaO2. 10,12 In this study, microalbuminuria was significantly more in COPD patients having PaCO2 ≥45 mmHg as compared to COPD patients having PaCO2 <45 10,12,13 In this study, 6MWD test was also observed and found that; as exercise capacity decreases, the prevalence of Microalbuminuria increases. Kumar et al, also obtained an inverse relationship of 6MWD with Microalbuminuria levels in their study.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…13 In the study of Mehmood and Sofi et al, and Agrawal et al, COPD patients having microalbuminuria were more hypoxic than those of COPD patients without microalbuminuria and it was inversely related to PaO2. 10,12 In this study, microalbuminuria was significantly more in COPD patients having PaCO2 ≥45 mmHg as compared to COPD patients having PaCO2 <45 10,12,13 In this study, 6MWD test was also observed and found that; as exercise capacity decreases, the prevalence of Microalbuminuria increases. Kumar et al, also obtained an inverse relationship of 6MWD with Microalbuminuria levels in their study.…”
Section: Discussionsupporting
confidence: 51%
“…A recent study by Agrawal et al, in 2017 observe prevalence of Microalbuminuria in COPD patients to be 46%. 10 In study of Bulcon et al, in 2013 found that prevalence of Microalbuminuria to be 39%. 11 Mehmood and Sofi et al, in 2015, were also found that MAB was more frequent in COPD patients compared to smokers without obstruction (20.6% vs. 7.4%, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…Treatment with enalapril blunted these effects in mice, suggesting a role of angiotensin I-converting enzyme (ACE) inhibitors for renal protection in patients with COPD (108). Agrawal et al also demonstrated increased albuminuria in patients with acute exacerbations of COPD (3).…”
Section: Effect Of Cigarette Smoke On Endothelial Apoptosis In Copdmentioning
confidence: 91%